Stabilizing the domestic price level under fluctuating terms of trade - Egbert Gerken (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
In this paper a general equilibrium model of Chile will be applied to quantify (a) the requirements for real exchange rate stabilization in a commodity exporting country, (b) the implications of nominal exchange rate and price level stabilization, and (c) short-run benefits and long-run costs of using compensatory finance. The analysis will be done under conditions of both a closed and an open capital account. The recent Chilean experience, which will be sketched in chapter II, provides an almost ideal case for such endeavour. The model will be outlined in chapter III and documented in the Appendix. Results will be presented in chapter IV and conclusions drawn in chapter V.
Keywords: 330